UPAYA MENINGKATKAN AKTIVITAS BELAJAR IPA BIOLOGI MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH BAGI SISWA KELAS VII F DI SMP NEGERI 6 SEMARANG - Sri Sarmini (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2011)
Electrical materials are difficult to understand by students. Although teachers are taking a variety of efforts such as the use of methods and approaches vary, but the results are still low / not maximized. It can also be seen from the acquisition of learning outcomes in science test scores rise in class VIII (UKK) purely academic year 2010/2011, a class VIII A gain value of 74.30, a class VIII B with a value of 72.66, a class VIII C 68.75 , a class VIII D 70.08, 77.03 E VIII class, a class VIII and class VIII F 76.67 G 64.52. There are still some unfinished class, whereas a minimum completeness criteria (KKM) VIII-class science subjects at 70. IX D grade students from all classes with a heterogeneous composition capable students. Not optimal learning outcomes related to science students in grade IX junior D 6 Semarang, the author seeks to apply a contextual approach to teaching and learning using electrical kit as an alternative means of learning that lead to active learning, creative, effective, and fun. This classroom action research aims to determine the increase in electrical material science learning outcomes and planting the creative character and curiosity through contextual approach to teaching and learning using electrical kit in grade IX D 6 Semarang semester junior year class 2011/2012. Data collection methods in this study using a written test and observation. Data analysis using descriptive techniques. Based on the results of research that has been implemented, it can be concluded that the contextual approach to teaching and learning to use an electric kit is proven to improve learning outcomes IPA electrical materials and planting the creative character and curiosity in students' junior class IX D 6 Semarang lessons Semester I 2011/2012. It marked the success indicators of achievement and classroom action research to an increase in the average results of the cycle I learned IPA at 77.67 to 92.80 in the second cycle. As for the achievement of individual learning thoroughness, I cycle of 77% and 96.7% for the second cycle. The process of learning science with a contextual approach to teaching and learning to use an electric kit also resulted in the creation of enjoyable learning. Students are more creative in learning and have a high curiosity in studying the electrical materials. Similarly, increasing the activity of teachers being able to manage the process of learning science is more active, innovative, creative, effective, and fun. Key words: learning the IPA, contextual approach to teaching and learning